Scraping By: Income and Program Participation After the Loss of Extended Unemployment Benefits - Jesse Rothstein; Robert G. Valletta (Institute for the Study of Labor (IZA), 2014)
Despite unprecedented extensions of available unemployment insurance (UI) benefits during the Great Recession of 2007-09 and its aftermath, large numbers of recipients exhausted their maximum available UI benefits prior to finding new jobs. Using SIPP panel data and an event-study regression framework, we examine the household income patterns of individuals whose jobless spells outlast their UI benefits, comparing the periods following the 2001 and 2007-09 recessions. Job loss reduces household income roughly by half on average, and for UI recipients benefits replace just under half of this loss. Accordingly, when benefits end the household loses UI income equal to roughly one-quarter of total pre-separation household income (and about one-third of pre-exhaustion household income). Only a small portion of this loss is offset by increased income from food stamps and other safety net programs. The share of families with income below the poverty line nearly doubles. These patterns were generally similar following the 2001 and 2007-09 recessions and do not vary dramatically by household age or income prior to job loss.
Keywords: J65; I38; 330; unemployment benefit exhaustion; household income; social program interactions